Excess Mortality Attributable to Hospital-Acquired Antimicrobial-Resistant Infections: A 2-Year Prospective Surveillance Study in Northeast Thailand. (20th June 2022) - Lim, Cherry; Teparrukkul, Prapit; Nuntalohit, Somboon; Boonsong, Somsamai; Nilsakul, Jiraphorn; Srisamang, Pramot; Sartorius, Benn; White, Nicholas J; Day, Nicholas P J; Cooper, Ben S; Limmathurotsakul, Direk
Abstract: Background: Quantifying the excess mortality attributable to antimicrobial-resistant (AMR) bacterial infections is important for assessing the potential benefit of preventive interventions and for prioritization of resources. However, there are few data from low- and middle-income countries. Methods: We conducted a 2-year prospective surveillance study to estimate the excess mortality attributable to AMR infections for all types of hospital-acquired infection (HAI), and included bacterial species that were both locally relevant and included in the World Health Organization priority list. Twenty-eight-day mortality was measured. Excess mortality and population attributable fraction (PAF) of mortality caused by AMR infections compared to antimicrobial-susceptible (AMS) infections, adjusted for predefined confounders, were calculated. Results: We enrolled 2043 patients with HAIs. The crude 28-day mortality of patients with AMR and AMS infections was 35.5% (491/1385) and 23.1% (152/658), respectively. After adjusting for prespecified confounders, the estimated excess mortality attributable to AMR infections was 7.7 (95% confidence interval [CI], 2.2–13.2) percentage points. This suggests that 106 (95% CI, 30–182) deaths among 1385 patients with AMR infections might have been prevented if all of the AMR infections in this study were AMS infections. The overall PAF was 16.3% (95% CI, 1.2%–29.1%). Among the bacteria under evaluation, carbapenem-resistant Acinetobacter baumannii was responsible for the largest number of excess deaths. Among all types of infection, urinary tract infections were associated with the highest number of excess deaths, followed by lower respiratory tract infections and bloodstream infections. Conclusions: Estimating and monitoring excess mortality attributable to AMR infections should be included in national action plans to prioritize targets of preventive interventions. Clinical Trials Registration: NCT03411538. Abstract : Burden of antimicrobial-resistant (AMR) bacterial infection is high in low- and middle-income countries. Data generated from prospective surveillance on multiple organisms and for every type of hospital-acquired infection could support prioritizing targets of preventive interventions to control the spread of AMR infection.